Transcriptomic and proteomic analyses provide insights into host adaptation of a bamboo-feeding aphid - Zhang, Hui; Lin, Ruixun; Liu, Qian; Lu, Jianjun; Qiao, Gexia; Huang, Xiaolei (Frontiers in Plant Science, 2023)
Introduction Salivary glands and their secreted proteins play an important role in the feeding process of sap-sucking aphids. The determination of saliva composition is an important step in understanding host plant adaptation of aphids. Pseudoregma bambucicola is a severe bamboo pest in subtropical areas and the only aphid species that can exclusively feed on hard stalks of bamboos. How this species can penetrate and degrade hard bamboo cell walls and utilize a very specialized niche are important unanswered questions. Methods In this study, comprehensive analyses based on transcriptome sequencing, RT-qPCR, liquid chromatography-tandem spectrometry (LC–MS/MS) and bioinformatics were conducted on dissected salivary glands and secreted saliva of P. bambucicola to characterize the overall gene expression and salivary protein composition, and to identify putative effector proteins important for aphid-plant interactions. Results and Discussion Some secretory proteins homologous to known aphid effectors important for aphid–plant interactions, such as digestive enzymes, detoxifying and antioxidant enzymes and some effectors modulating plant defenses, are also detected in salivary gland transcriptome and salivary gland and/or saliva secretomes in P. bambucicola. This indicates that these effectors are probably be essential for enabling P. bambucicola feeding on bamboo host. Although several plant cell wall degrading enzymes (PCWDEs) can be identified from transcriptome, most of the enzymes identified in salivary glands showed low expression levels and they only represent a small fraction of the complete set of enzymes for degrading cellulose and hemicellulose. In addition, our data show that P. bambucicola has no its own ability to produce pectinases. Overall, our analyses indicate that P. bambucicola may lose its own ability to express and secrete key PCWDEs, and its adaptation to unique feeding habit may depend on its symbiotic bacteria.